Optimalisasi Media Digital Interaktif Edpuzzle Dan Strategi Kesantunan Berbahasa Sebagai Upaya Preventif Bullying Pada Anak Sekolah Dasar Di SD Negeri 162107 - Christina Natalina Saragi; Irmina Pinem; Golbed Harmuda Diva Sinaga; Apriani Silviani Sitinjak; Amelia Zai (LPPM Universitas HKBP Nommensen, 2025)
Abstract Bullying in elementary schools is a serious issue that can negatively impact children's development. This study aims to explore the use of interactive digital media, specifically Edpuzzle, as a preventive measure against bullying by enhancing language politeness. Conducted at SD Negeri 162107 Tebing Tinggi, this research involved training teachers in the use of Edpuzzle to deliver material on language politeness. The method employed was the creation of interactive videos that educate students about the importance of polite language and the impacts of bullying. The training results showed an increase in teachers' understanding of using Edpuzzle, as well as a high interest from students in the material presented. The interactions that occurred during the learning process created a positive classroom atmosphere, thereby reducing the potential for bullying. The conclusion of this study indicates that Edpuzzle is effective in raising awareness of language politeness among students. It is recommended that schools continue to integrate technology into learning and conduct further socialization regarding the importance of language politeness to prevent bullying. Keywords: Edpuzzle, bullying, language politeness, digital media, education